Microscale and macroscale modeling of microalgae cultivation in photobioreactor: A review and perspective - Khoo, C.G. (Elsevier, 2019)
Mathematic modeling played an important role in optimizing the performance of photobioreactor (PBR) for cell cultivation. Based on the fundamental principles of microalgae cultivation systems, the current developed mathematic models include the microscale (growth kinetic of cells) and macroscale (transport phenomena in PBR). The mathematical models are aimed to provide an insight of the combination effects between the microalgae growth kinetic and transport phenomena within the PBR system. Up to now, the developed mathematical models are theoretically driven and statistically tractable, which is applicable to scale-up microalgae cultivation systems. The insights to the qualitative understanding of PBR optimization have been achieved through improvement of modeling works, which are through the efforts of laboratory-scale experiments and field study. In this chapter, the discussions are focused on the sensitivity of the model input parameters, comparison between the predicted microalgae productivity within literature, and analysis of the influences of transport phenomenon with microalgae growth kinetics within the PBR cultivation system through model validation. Â© 2019 Elsevier Inc. All rights reserved.